Studi Komparatif Literasi Saintifik Guided Inquiry VS Free Inquiry Pada Materi Zat dan Perubahannya - Elfiana, Nia; Kusuma, Mobinta; Widiyanto, Bayu (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2024)
This research aims to compare the influence of guided inquiry and free inquiry models on scientific literacy abilities. The method used in this research is counterbalanced with a one group pretest-posttest design. The population in this study were students in class The sampling technique is purposive sampling. Data collection techniques are tests (pretest-posttest) and non-tests. The data analysis used was the paired sample t-test, Cohen's d effect size test with the help of IBM SPSS V.25 software. The research results show that the paired sample t-test states that Ha is accepted, meaning there is a difference in scientific literacy abilities with the guided inquiry and free inquiry models with sig, 0.000. The Cohen's d test in the guided inquiry model treatment class obtained a value of 1.09, this score was higher compared to students who used the free inquiry model with a Cohen's d value of 0.12. The results of data analysis show that the Guided Inquiry model has more influence on students' scientific literacy abilities compared to the Free Inquiry model.